2019
DOI: 10.1080/10942912.2019.1642915
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and structure of myofibrillar protein extracted from Oratosquilla oratoria muscle as affected by ultra-high pressure

Abstract: Oratosquilla oratoria rich in myofibrillar protein is often shelled, but traditional methods of shelling have certain limitations. In order to better apply the ultra-high pressure (UHP) technology for shelling, the effects of UHP on rheological properties and structure of myofibrillar protein (MP) from O. oratoria treated with a pressure of 300-400 MPa were determined by rheometer and circular dichroism spectrometer. The results showed that in the frequency ramp tests using rheometer, the complex viscosity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The η indicates the bonding ability of materials (Liu et al, 2017). Figure 5 shown that all samples exhibited the phenomenon of shear thinning that the viscosity decreased with shear rates increasing (Li et al, 2019). The samples with shear thinning could promote the process of squeezing out form barrel.…”
Section: Dominated Solid Properties Of Rheology In Surimi By Heatingmentioning
confidence: 96%
See 2 more Smart Citations
“…The η indicates the bonding ability of materials (Liu et al, 2017). Figure 5 shown that all samples exhibited the phenomenon of shear thinning that the viscosity decreased with shear rates increasing (Li et al, 2019). The samples with shear thinning could promote the process of squeezing out form barrel.…”
Section: Dominated Solid Properties Of Rheology In Surimi By Heatingmentioning
confidence: 96%
“…According to method of Li et al (2019), 1 g of surimi mixing with 5 ml solutions of A, B, C, D, E to made five different solutions separately which A, B, C, D, and E were 0.05 mol L À1 NaCl, 0.6 mol L À1 NaCl, a mixture of 0.6 mol L À1 NaCl and 1.5 mol L À1 urea, a mixture of 0.6 mol L À1 NaCl and 8 mol L À1 urea, and a mixture of 0.6 mol L À1 NaCl, 8 mol L À1 urea and 0.05 mol L À1 β-mercaptoethanol, respectively. After stilling on the stand at 4 C for 1 h, samples were centrifuged at 10,000 rpm for 15 min.…”
Section: Determination Of Chemical Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have successfully improved the physicochemical properties of WBMP using glycosylation ( Wang et al, 2022d ), high-intensity ultrasound ( HIU ), and preheating technology ( Wang et al, 2022a ). Other methods that have been reported to change the structure and solubility of proteins include ultra-high pressure ( Li et al, 2019a ) and pH-shifting ( Li et al, 2022 ). Among these, pH-shifting and HIU are 2 commonly used and effective techniques.…”
Section: Introductionmentioning
confidence: 99%